2005
DOI: 10.1097/01.yct.0000166634.73555.e6
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Practice of Electroconvulsive Therapy in Teaching Hospitals in India

Abstract: More than 70% of ECT administrations in India were performed in the psychiatric hospitals. Approximately half of ECT use was unmodified ECT. The majority of patients who received ECT were diagnosed with schizophrenia and major depression. ECT training programs for psychiatry residents were acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
1
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 15 publications
6
70
1
7
Order By: Relevance
“…This is in contrast to the findings from Asian studies which show that schizophrenia is the commonest diagnosis among patients receiving ECT. A survey [16] of practice of ECT in India showed that Patients with schizophrenia received ECT most frequently (36.5%), followed by patients with major depression (33.5%), mania (17.9%) and a similar trend has also been reported for Asian countries by the same group of authors [8]. The finding of our study was consistent with the finding of these surveys as majority of patients receiving ECT in our study were suffering from Schizophrenia.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This is in contrast to the findings from Asian studies which show that schizophrenia is the commonest diagnosis among patients receiving ECT. A survey [16] of practice of ECT in India showed that Patients with schizophrenia received ECT most frequently (36.5%), followed by patients with major depression (33.5%), mania (17.9%) and a similar trend has also been reported for Asian countries by the same group of authors [8]. The finding of our study was consistent with the finding of these surveys as majority of patients receiving ECT in our study were suffering from Schizophrenia.…”
Section: Resultssupporting
confidence: 83%
“…Direct ECT is very commonly used in many parts of the world accounting for the largest ECT population in the world [15]. In a survey [16] conducted in Indian teaching hospitals, 10,234 patients (52% of total patients) received 52,450 unmodified ECT treatments (46% of total number of treatments) at 33 institutions. Unmodified ECT was always used in 20 institutions.…”
Section: Resultsmentioning
confidence: 99%
“…Na amostra, essa categoria corresponde a 47,8%, característica essa semelhante no Japão 20 (40,4%) e na Índia 21 (43,9%). Nos países em que há preponderância de depressão 18,19,23,24 , a faixa etária dos pacientes que realizam ECT é razoavelmente mais alta que a do Brasil 7,8,12 , do Japão 20 e da Índia 21 , onde foi encontrada maior prevalência diagnóstica de esquizofrenia. Isso pode ser entendido pelo acometimento mais precoce da esquizofrenia em relação à depressão.…”
Section: Resultsunclassified
“…Bu bulgu ülkemiz ve Asya ülke verileri ile benzer, Batý verileri ile terslik gösterir (9,12,14). Bunun sebebi geliþmekte olan ülkelerde erkeklerin saðlýk hizmetlerine daha çok ulaþabilmesi ve hizmetlerden daha çok yararlanabilmesi ile EKT uygulamalarý sýrasýnda cinsiyetler arasý bir bias olabilir.…”
Section: Tartiþmaunclassified